Gene expression dynamics in fibroblasts during early-stage murine pancreatic carcinogenesis - Nupur Ohri; Johanna Häußler; Nino Javakhishvili; David Vieweg; Anais Zourelidis; Bogusz Trojanowicz; Monika Haemmerle; Irene Esposito; Markus Glaß; Yoshiaki Sunami; Jörg Kleeff (iScience)
Summary: Pancreatic ductal adenocarcinoma (PDAC) is characterized by aggressive growth and metastasis, partly driven by fibroblast-mediated stromal interactions. Using RNA sequencing of fibroblasts from early-stage KPC mouse models, we identified significant upregulation of genes involved in adipogenesis, fatty acid metabolism, and the ROS pathway. ANGPTL4, a key adipogenesis regulator, was highly expressed in fibroblasts and promoted pancreatic cancer cell proliferation and migration through paracrine signaling. Notably, cancer cell-driven paracrine signals appear to regulate ANGPTL4 expression in fibroblasts, suggesting that ANGPTL4 may act as a reciprocal factor in a feedback loop that enhances tumor progression. LAMA2, an extracellular matrix gene with reduced expression, suppressed pancreatic cancer cell migration, proliferation, and invasion. This study provides the temporal transcriptional analysis of fibroblast subtypes during early PDAC, highlighting the roles of metabolic reprogramming and ECM remodeling in shaping the tumor microenvironment and identifying potential therapeutic targets.